Peran Bhabinkamtibmas Dalam Melaksanakan Penyuluhan Guna Mencegah Tindak Pidana Curanmor Di Wilayah Hukum Polsek Lembang - Yudha, Charlie (Police Studies Review, 2020)
The focus of this thesis research is motivated by theft which is very frequent. The most common crime of theft is motor vehicle theft. Some of the factors that led to the occurrence of curanmor crimes, among others, were caused by the increasing number of unemployed and dropping out of school children, limited members of community protection (Linmas), inactive social organizations and the increasing number of motorized vehicles themselves. In terms of handling cases as he said, the preemptive efforts carried out by the National Police in the form of counseling to all levels of society, especially motorbike users, are very necessary, namely by developing community participation in efforts to prevent opportunities and opportunities for criminals to commit theft of weight. and violent theft with two-wheeled motorized vehicles. This is where the role and function of Binmas is demanded to carry out preemptive efforts. One of them is in the form of counseling by Bhabinkamtibmas as the foremost executor of the Binmas function to carry out its main duties in the frontier regional unit. The theories and concepts used to analyze and answer problems. The role of Bhabinkamtibmas in implementing counseling is Role theory and management theory. The research method used by the author is field research using a qualitative approach, and the author's data collection techniques are by interview, observation, and document study. Based on the research results, it was found that the implementation of outreach to the community still encountered obstacles. There are several inhibiting factors in the implementation of counseling in realizing Harkamtibmas. Factors that become obstacles in the implementation of counseling are man, money, material, market factors. The author provides advice to the Cimahi Police, precisely the Lembang Police, to conduct counseling by taking an active role and also overcoming external and internal factors. Likewise with stake holders Able to evaluate and analyze implementation according to Perkap and SOP.